, , , , , , , , , , , , , , , , , , , , , , , , , , .
ENG
 

            

. . ()  

. . ()

 

( )2 = 2 2 + 2

( )3 = 3 32 + 32 3

2 - 2 = ( + ) ( - )

3 + 3 = ( + ) (2 - + 2)

3 - 3 = ( - ) (2 + + 2)

( + + )2 = 2 + 2 + 2 +2 +2 +2

.

= +

: = -

() =

() =

( : ) = :

- = 1 :

: = Ö

.

Ö =Ö Ö

Ö Ö = Ö

Ö : = Ö : Ö

(Ö) = Ö

Ö = /

ÖÖ = Ö

(Ö) = Ö

.

1, 2, 3, , n-1, n

n-1 - n = d

d 蠠

2 = 1+ d

3 = 2 + d = 1 + 2d

n = 1 + d(n-1)

Sn = (1 + n) n = (21 + ( n-1) d) n

2 2

Sn 頠

.

d .

d > 0

d < 0 .

.

1, 2, 3, , n-1, n

n+1 / n = q

2 = 1 q

q - .

3 = 2 q = 1 q2

n = 1 q n-1

(q > 1)

Sn = n q - 1 = 1 (qn -1 : q 1)

q 1

(q < 1)

Sn = 1 (1 - qn)

1 - q

Sn = 1

1 - q

.

= 12 ={2 1, 2 1, z2 z1}

ç ç=Ö(2 - 1)2 +(2 - 1)2 + (z2 - z1)2

a = d

= ç çç çcos j

cos j = 12 + 12 + z1z2

Ö12 + 12 +z12 Ö22 +22 + z22

2 = ç ç2

= 12 + 12 + z1z2

çç, 1 = 1 = z1

2 2 z2

^ , 12 + 12 + z1z2

.

(c u)¢ = u¢

u ¢ = u¢ v u v¢

v v2

(c)¢ = 0

(xn )¢ = n xn-1

(ax)¢ = ax ln a

( )¢ =

(sin x)¢ = cos x

(cos x)¢ = - sin x

(tg x)¢ = 1

cos2 x

(ctg x)¢ = - 1

sin2 x

(ln x)¢ = 1

(1 / )¢ = - 1

2

(Ö)¢ = 1

2 Ö

()¢ = 1

.

log = 񠠠

log 1 = 0

log = 1

log (m n) = log m + log n

log m = log m - log n

n

log m n = n log m

log n Öm = 1 log m

n

log = log

log


sin2x + cos2x = 1

tg x = sin x

cos x

ctg x = cos x

sin x

1 + ctg2 x = 1

sin2 x

1 + tg2 x = 1

cos2 x

tg x ctg x = 1

sin (a b) = sina cosb cosa sinb

cos (a b) = cosa cosb sina sinb

tg (a b) = (tga tgb)

(1 + tga tgb)

ctg (a b) = ctga ctgb + 1

ctgb ctga


sina + sinb = 2 sin (a + b) cos (a - b)

2              2

sina - sinb = 2 cos (a + b) sin (a - b)

2              2

cosa + cosb = 2 cos (a + b) cos (a - b)

2              2

cosa - cosb = - 2 sin (a + b) sin (a - b)

2              2

tga tgb = sin (a b)

cosa cosb

ctga ctgb = sin (b a)

sina sinb

sin2a - sin2b = cos2b - cos2a =

sin (a + b) sin (a - b)

cos2a - sin2b = cos2b - sin2a =

cos (a + b) cos (a - b)

sina = Ö1 - cos2a

sina = tga

Ö1 + tg2a

sina = 1

Ö1 + ctg2a


cosa = Ö1 - sin2a

cosa = 1

Ö1 + tg2a

cosa = ctga

Ö1 + ctg2a


tga = sina

Ö1 - sin2a

tga = Ö1 - cos2a

cosa

tga = 1

ctga


ctga = Ö1 - sin2a

sina

ctga = cosa

Ö1 - cos2a

ctga = 1

tga

sina sinb = cos (a - b) - cos (a + b)

2

cosa cosb = cos (a - b) + cos (a + b)

2

sina cosb = sin (a + b) + sin (a - b)

2

tga tgb = tga + tgb

ctga + ctgb

ctga tgb = ctga + tgb

tga + ctgb

ctga ctgb = ctga + ctgb

tga + tgb

sin2a = 2 sina cosa

sina = 2 sin (a) cos (a)

cos2a = cos2a - sin2a =

= 1 - 2sin2a =

= 2cos2a - 1

tg2a = 2 tga

1 - tg2a

= 2

ctga - tga

tga = 2 tg (a/2)

1 - tg2 (a/2)

ctg2a = ctg2a - 1

2 ctga

= ctga - tga

2

ctga = ctg2 (a/2) - 1

2 ctg (a/2)

sin x = a

x = (-1)n arksin a + pn


cos x = a

x = arkcos a + 2pn


tg x = a

x = arktg a + pn


ctg x = a

x = arkctg a + pn

sin (p /2 - a) = + cosa

sin (p /2 + a) = + cosa

sin (p - a) = + sina

sin (p + a) = - sina

sin (3p/2 - a) = - cosa

sin (3p /2 + a) = - cosa

sin (2p - a) = - sina

sin (2p + a) = + sina

----------------

cos (p/2 - a) = + sina

cos (p/2 + a) = - sina

cos (p - a) = - cosa

cos (p + a) = - cosa

cos (3p/2 - a) = - sina

cos (3p/2 + a) = + sina

cos (2p - a) = + cosa

cos (2p + a) = + cosa

-----------------

tg (p/2 - a) = + ctga

tg (p/2 + a) = - ctga

tg (p - a) = - tga

tg (p + a) = + tga

tg (3p/2 - a) = + ctga

tg (3p/2 + a) = - ctga

tg (2p - a) = - tga

tg (2p + a) = + tga

-------------

ctg (p/2 - a) = + tga

ctg (p/2 + a) = - tga

ctg (p - a) = - ctga

ctg (p + a) = + ctga

ctg (3p/2 - a) = + tga

ctg (p/2 + a) = - tga

ctg (2p - a) = - ctga

ctg (2p + a) = + ctga

sin (- a) = - sina

cos (- a) = cosa

tg (- a) = - tga

 



a2 + b2 = c2

a = c sina

a = b tga

b = c cosa

:

a = b = c

sina sinb sing

:

a2 = b2 + c2 - 2 bc cosa

S = ½ ab

S = a b = ½ d1 d2 sina,

d1 d2 -

a -

S = a h = a b sina

S = ½ d1 d2 sina

S = a + b h = ½ d1 d2 sina

2

S = l r = p r2

2

S = ½ ah = ½ ab sina

:

S = Ö p (p - a) (p - b) (p - c)

p = a +b + c

2

:

S = a b c

4r

:

S = ½ r P

:

R = a b c

4S

:

r = 2S

a + b + c

:

l = 2pr

S = a2 = d2/2

S = a2 sina = ah = ½ dD

d -

D -

:

V = S h

V = abc = a3

V = S h = S^ l

l -

V = 1/3 S h

V = S h = p r2 h = 1/4p d2 h

r -

d -

V = 1/3 S h = 1/3 p r2 h

V = 4/3 p r3

S = S + 2S

S = ph = S^ l

p = a + b +c

S = 6a2

S = S + S

S = ½ P h

h

S = S + S

S = S cosj

j -

S = S + S

S = 2p rh

S = 2pr (h + r)

S = S + S

S = prl

S = pr (l + r)

S = S + 2S

S = P l

S = 4 pr2

a 0 p/6 p/4 p/3 p/2 p

sin 0 ½ Ö2/2 Ö3/2 1 0

cos 1 Ö3/2 Ö2/2 ½ 0 -1

tg 0 1/Ö3 1 Ö3 - 0

ctg - Ö3 1 1/Ö3 0 -

























































































© 2010.